The World Trade Center Health Program: Petitions for adding qualifying health conditions. Issue 10 (15th June 2021) - Daniels, Robert D.; Carreón, Tania; Bilics, Jessica A.; Reissman, Dori B.; Howard, John
Abstract: The federally mandated World Trade Center Health Program provides limited health benefits for qualifying health conditions related to the 9/11 terrorist attacks. A qualifying health condition is an illness or health condition for which the member's exposure to airborne toxins, any other hazard, or any other adverse condition resulting from the 9/11 terrorist attacks is considered substantially likely to be a significant factor in aggravating, contributing to, or causing the illness or health condition. These qualifying health conditions are listed in federal regulations. The regulations also provide a process for amending this list. This commentary describes the methods developed for adding health conditions to the list of qualifying health conditions and discusses changes to the list that have occurred during the Program's 2011–2020 period.